2016
DOI: 10.1111/jpn.12577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling whole crop oat with lucerne in different ratios on fermentation quality, aerobic stability and in vitro digestibility on the Tibetan plateau

Abstract: The objective of this study was to determine the effect of ensiling different ratios of whole crop oat to lucerne on fermentation quality, aerobic stability and in vitro digestibility of silage on the Tibetan plateau. Four experimental treatments were produced varying in the ratio of forages on a fresh matter (FM) basis: 1) 100% oat (control, dry matter (DM) content: 317 g/kg), 2) 90% oat + 10% lucerne (OL10, DM content: 316 g/kg), 3) 80% oat+ 20% lucerne (OL20, DM content: 317 g/kg) and 4) 70% oat+ 30% lucern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…This may explain the linear decrease ( p < .05) in EE content in alfalfa and SS silages as the proportion of SS increased. Ordinarily, a pH decline accompanies an increase in organic acids during ensiling, with a higher proportion of gramineous plants, such as oats, corn, and SS, in mixed silage resulting in higher lactic acid content (Chen et al, ; Wang, Yu, Wu, & Hannaway, ; Zhang et al, ). However, it was surprising to note that the lactic acid contents in corn or SS pure silage were not higher ( p < .05) than the silages including alfalfa, instead were lower ( p < .05) than some treatments, and this was consistent with the findings of Wang et al (), who found that the inclusion of legumes in silages resulted in higher lactic acid content than that in pure corn silage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the linear decrease ( p < .05) in EE content in alfalfa and SS silages as the proportion of SS increased. Ordinarily, a pH decline accompanies an increase in organic acids during ensiling, with a higher proportion of gramineous plants, such as oats, corn, and SS, in mixed silage resulting in higher lactic acid content (Chen et al, ; Wang, Yu, Wu, & Hannaway, ; Zhang et al, ). However, it was surprising to note that the lactic acid contents in corn or SS pure silage were not higher ( p < .05) than the silages including alfalfa, instead were lower ( p < .05) than some treatments, and this was consistent with the findings of Wang et al (), who found that the inclusion of legumes in silages resulted in higher lactic acid content than that in pure corn silage.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the linear decrease (p < .05) in EE content in alfalfa and SS silages as the proportion of SS increased. Ordinarily, a pH decline accompanies an increase in organic acids during ensiling, with a higher proportion of gramineous plants, such as oats, corn, and SS, in mixed silage resulting in higher lactic acid content (Chen et al, 2017;Wang, Yu, Wu, & Hannaway, 2018;Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The dried pre‐ensiled material and silage samples were analyzed for DM (934.01), CP (984.13), ash (942.05) and ether extract (EE) (920.39) in accordance with the methods of Association of Official Analytical Chemists . The WSC were determined using the method of Chen et al . Ash free neutral detergent fiber (NDF; with heat stable α‐amylase), ash free acid detergent fiber (ADF) and acid detergent lignin (ADL) were sequentially performed in accordance with the procedure of Van Soest et al .…”
Section: Methodsmentioning
confidence: 99%
“…For the microbial counts, 10 g of the sample was ten‐fold serially diluted with sterilized saline solution (0.85% NaCl). LAB, yeasts and moulds were enumerated using the method of Chen et al . The yeast and mould colonies were enumerated separately, according to their morphological appearance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation